Niveles de comprensión lectora en alumnos del quinto grado de primaria de una institución educativa de Bellavista - Callao - Vega Vásquez, César Hugo (2012)
The investigation of not experimental type used a descriptive simple design, which intention was identified the levels of reading comprehension in the students of 5to degree of primary of an educational institution of the district of Bellavista - Callao. It was considered to be a sample not probabilística of 85 pupils. The categories of qualification are established for the variable reading comprehension, as well as his four dimensions which were evaluated by a test of reading comprehension ACL5 of Catalá, Catalá, Catalá, Molina and Monclús (2001) adapted by the author (2009). The results demonstrated that the literal dimension evaluated in the sample presents a low range in 52,9 %, the dimension inferencial evaluated is low in 49,4 %, the dimension criterial with an average range of 35,3 % and the capacity of reorganization of reading comprehension is low in 71,8 % of consulted subjects. In the general evaluation of the reading comprehension the index of approval presents an average range of 68,2 % of the sample.